2002
DOI: 10.1183/09031936.02.00088702
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality and daytime function in adults with cystic fibrosis and severe lung disease

Abstract: It was hypothesized that adult cystic fibrosis (CF) patients with severe lung disease have impaired daytime function related to nocturnal hypoxaemia and sleep disruption.Nineteen CF patients (forced expiratory volume in one second 28¡7% predicted) and 10 healthy subjects completed sleep diaries, overnight polysomnography (PSG), and assessment of daytime sleepiness and neurocognitive function.CF patients tended to report more awakenings (0.7 ¡ 0.5 versus 0.3 ¡ 0.2?h -1 , p=0.08), and PSG revealed reduced sleep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
76
1
3

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 29 publications
6
76
1
3
Order By: Relevance
“…Secondly, our control subjects were children and adolescents who underwent a sleep study in our sleep laboratory and were found to have normal study. [5,[14][15][16]. All of these studies focused only on adult population.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Secondly, our control subjects were children and adolescents who underwent a sleep study in our sleep laboratory and were found to have normal study. [5,[14][15][16]. All of these studies focused only on adult population.…”
Section: Discussionmentioning
confidence: 97%
“…Spier et al [7] demonstrated that CF patients had reduced SE and REM sleep. In addition, sleep disruption and subsequent impairment in daytime function were found to be related to nocturnal hypoxemia [5]. However, there is little data on the sleep quality and sleep architecture in children with CF.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Existem poucos estudos que abordam a arquitetura do sono na população de pacientes com FC e sobre a prevalência de DRS em pacientes com FC, especialmente de SAOS em crianças com FC 5 . A maioria dos dados publicados na literatura sobre DRS e FC baseia-se em estudos com populações mais velhas: pacientes no final da adolescência ou adultos jovens 18 . O presente estudo avaliou uma população de pacientes mais jovem (mediana da idade de 8 anos, amplitude de 5 a 10 anos).…”
Section: Discussionunclassified